Assessment the Potential of SRES Scenario for Kuala Sala, Malaysia - Nurul Nadrah Aqilah, Tukimat; Nor Azlina, Alias (International Organization of Scientific Research (IOSR), 2016)
The diversity of SRES scenarios that has potential to produce different increment of climatic trend reflects to the future expectation on development patterns. The selection of an appropriate emission scenario is important to present the appropriate climatic trend suit to the site study. The main objective is to determine appropriate emission scenarios and potential increment of rainfall in the upcoming year Δ2020 and Δ2050 for site study. Two climate projection models; SDSM and PRECIS models were used to generate the future rainfall trends using A2, B2 and A1B scenarios. The result showed the B2 scenario has potential to produce similar trend to the historical for the Kuala Sala station, in Kedah, followed by the A2 scenario. Scenario A1B is estimated to underestimate/overestimate through a year affected by the coordinate gap selection of site study. Generally, the annual rainfall intensity predicted varies for different SRES scenarios and reflect to the future expectation on development patterns. The highest rainfall increment is predicted by using the B2 scenario (about 2638mm/year) until year Δ2050. A1B is predicted to produce the lowest increment. The heaviest monthly rainfall, predicted to occur twice a year, is influenced by the seasonal monsoon effects. This study proved that different emissions will produce diverse rainfall trends due to the influence of greenhouse gases.